TELAAH PERKAWINAN SETELAH KEHAMILAN DALAM KITAB HUKUM ISLAM KARYA PROF.DR H. SUPARMAN USMAN, S.H - Mawar Pertiwi; Nur Habiba (Al Qadhi, 2023)
Building on the phenomenon of Generation Z regarding common marriage practices during pregnancy, this research examines the meaning derived from sources in the Islamic legal book of Indonesia. Scholars consider various legal aspects, emphasizing their own interpretations of the pillars of Islamic law. This observation, made by contemplating the beautiful verses of Allah in the Qur'an and the words and actions of the Prophet in the Hadith, provides insights for legal practitioners and researchers. It also establishes a foundation for just and Islamic principle-aligned policies concerning the legality of such actions from an Islamic perspective.